Osteoporosis in Inflammatory Arthritides: New Perspective on Pathogenesis and Treatment - Rotta, Denise; Fassio, Angelo; Rossini, Maurizio; Giollo, Alessandro; Viapiana, Ombretta; Orsolini, Giovanni; Bertoldo, Eugenia; Gatti, Davide; Adami, Giovanni (Frontiers in Medicine, 2020)
Inflammatory arthritides are frequently associated to systemic skeletal complications, such as osteoporosis and fragility fractures. Herein, we presented a review of the available literature on osteoporosis in inflammatory arthritides, with a special focus on Rheumatoid Arthritis (RA), Psoriatic Arthritis (PsA) and Spondyloarthritides (SpA). We also concentrated on the effects of anti-osteoporotic medications on the skeletal involvement in such diseases and on the effects of anti-rheumatic treatments on bone heath and fracture incidence